Biblical sermons how twelve preachers apply the principles of "Biblical preaching" - Robinson, Haddon W.; Robinson, Haddon W. (Grand Rapids, MI Baker, 1989)
Includes bibliographical references.
Keywords: Sermons -- history and criticism